Amyloidosis of the Breast with Multicentric DCIS and Pleomorphic Invasive Lobular Carcinoma in a Patient with Underlying Extranodal Castleman's Disease. (4th February 2013) - Chiang, David; Lee, Michael; Germaine, Pauline; Liao, Lydia
Abstract : We present an interesting case of focal amyloidosis of the left breast which was intermixed with ductal carcinoma in situ (DCIS). On subsequent staging bilateral breast magnetic resonance imaging (MRI), the patient was found to have an additional suspicious enhancing mass with spiculated borders within the left breast. This mass was biopsy proven to represent pleomorphic invasive lobular carcinoma. A pulmonary nodule within the lingula was also noted on the staging bilateral breast MRI and was biopsy proven to represent extranodal Castleman's disease. Therefore, it is believed that our patient had secondary amyloidosis due to Castleman's disease.